2021
DOI: 10.3390/rs13142825
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Wind-Wave Breaking by Long Surface Waves

Abstract: This paper reports the results of field measurements of wave breaking modulations by dominant surface waves, taken from the Black Sea research platform at wind speeds ranging from 10 to 20 m/s. Wave breaking events were detected by video recordings of the sea surface synchronized and collocated with the wave gauge measurements. As observed, the main contribution to the fraction of the sea surface covered by whitecaps comes from the breaking of short gravity waves, with phase velocities exceeding 1.25 m/s. Aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…This supports the amplitude analysis presented in Section 5.2, which showed enhanced breaking activity linked to the passage of energetic wave groups. Dominant wave crests have also been shown to be the preferential breaking regions for waves of various scales in previous field studies (Donelan et al, 1972;Dulov et al, 2002Dulov et al, , 2021Holthuijsen & Herbers, 1986;Yurovsky et al, 2017). A marked contrast exists, however, between the magnitude of long wave modulation of wave breaking in our results, which show a 2-5 fold enhancement of breaking probability attributed to wave groups, compared to those of Dulov et al (2002Dulov et al ( , 2021 who found modulation factors as high as 20-24.…”
Section: Comparison To Prior Observationsmentioning
confidence: 84%
See 3 more Smart Citations
“…This supports the amplitude analysis presented in Section 5.2, which showed enhanced breaking activity linked to the passage of energetic wave groups. Dominant wave crests have also been shown to be the preferential breaking regions for waves of various scales in previous field studies (Donelan et al, 1972;Dulov et al, 2002Dulov et al, , 2021Holthuijsen & Herbers, 1986;Yurovsky et al, 2017). A marked contrast exists, however, between the magnitude of long wave modulation of wave breaking in our results, which show a 2-5 fold enhancement of breaking probability attributed to wave groups, compared to those of Dulov et al (2002Dulov et al ( , 2021 who found modulation factors as high as 20-24.…”
Section: Comparison To Prior Observationsmentioning
confidence: 84%
“…Dominant wave crests have also been shown to be the preferential breaking regions for waves of various scales in previous field studies (Donelan et al, 1972;Dulov et al, 2002Dulov et al, , 2021Holthuijsen & Herbers, 1986;Yurovsky et al, 2017). A marked contrast exists, however, between the magnitude of long wave modulation of wave breaking in our results, which show a 2-5 fold enhancement of breaking probability attributed to wave groups, compared to those of Dulov et al (2002Dulov et al ( , 2021 who found modulation factors as high as 20-24. It is, however, important to keep in mind that our analysis sorts long waves into two categories, namely wave groups and the "background" wave field.…”
Section: Comparison To Prior Observationsmentioning
confidence: 84%
See 2 more Smart Citations
“…where h(x * ) is the Heaviside function with x * = c p /(1 − δ) − c T , chosen so Q p vanishes when c of the entire spectral peak region are below c T set to 2 m s −1 , constant b 1 corresponds to our experimental data (6), constant b 2 = 1.39 × 10 −5 is chosen to match the data reported in [35] (see their Figure 4). The exponent n is set to 5 to be consistent with [62] and with the experimental findings of [35,63]. An example of model simulations of Q using ( 16) as a function of the wind speed for various α and p is shown in Figure 11.…”
Section: Semi-empirical Expression For Qmentioning
confidence: 99%